Treinamento de resistência muscular inspiratório em indivíduos submetidos à hemodiálise: ensaio clínico randomizado - Zanini, Sheila Cristina Cecagno (2015)
Introduction: Individuals with chronic kidney disease (CKD) have complex changes due to the progressive decrease in the glomerular filtration rate, especially in the muscle structure and function. This study was designed from the results of a previous study, which was carried out inspiratory muscle training in a group with 40% load of MIP and the other with low load, was obtained as a result a better effect on muscle strength of the group with low. Objective: The aim of this study was to vestigate the effect of inspiratory muscle endurance training (IMET) in respiratory muscle strength and physical activity level in patients with CKD undergoing hemodialysis (HD). Methods: A randomized controlled trial, single blind, were carried out in 28 indivuduals with CKD undergoing HD, who were randomly divided into controlled group (n=15) and intervention group (n=13). The intervention group received IMET for 12 weeks with load of 10% MIP with at least -7 c H2O during 30 minutes. The study was approved by the Ethics Committee on Research in Human Beings, protocol number 614.198/2014. Results: The age mean from control group was 47.8±18.6 and 52.3±14.8 for the intervention group. The IMET had no significant effect on respiratory muscle strenght MIP (p=0.18) and MEP (p=0.98), on respiratory muscle endurance MVV (p=0.79), maximal functional capacity VO2max (p=0.67) and submaximal 6WT (p=0.59), pulmonary function FVC (p=0.51), FEV1 (p=0.27) e FEV1/FVC (p=0.21) and physical activity level (p=0.69). Discussion: IMET for 12 weeks did no increase the variables studied due to the load offered to patients was low and their respiratory muscles can tolerate greater inspiratory load without suffering muscle fatigue. Even without improvement in the physical activity level of these patients, the number of active individuals increased in both groups. The low consent of the individuals to participate in theproposed training was a limitation of this study. The physiotherapist has an important role in the hemodialysis unit and becoming a member of this team may offer benefits in the daily life of these patients. Conclusion: Patients with chronic kidney disease undergoing hemodialysis showed no improvement in respiratory muscle strength and endurance, functional capacity, pulmonary function and physical activity level after inspiratory muscle endurance training